THE INFLUENCE OF ORGANIZATIONAL CULTURE, SUPERVISION AND ENVIRONMENTAL WORK TOWARDS DISCIPLINE OF SUKARESMI VILLAGE EMPLOYEES - Catur Kironi (SMBJ: Strategic Management Business Journal, 2022)
Each organization is required to be able to optimize human resources and human resources who are able to work hard and have high productivity. Achieving high productivity is not an easy thing to do. An important factor for achieving high productivity is the implementation of work discipline from its employees. Organizational Culture, Supervision and work environment influence on Work Discipline of Sukaresmi Village Employees, East Cikarang Based on the partial test results, the t-test results for the organizational culture Supervision and work environment variable obtained partially that organizational culture Supervision and work environment have an effect on the work discipline of Sukaresmi Village employees